Genetic variation in the Vitamin D pathway CYP2R1 gene predicts sustained HBeAg seroconversion in chronic hepatitis B patients treated with pegylated interferon: A multicenter study - Kessarin Thanapirom (2018)
© 2017 Thanapirom et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Evidence of a role of Vitamin D in the immune system is increasing. Low serum Vitamin D is associated with increased hepatitis B virus replication. Genome-wide association study (GWAS) data has revealed a number of the single nucleotide polymorphisms (SNPs) within the Vitamin D synthetic pathway that affect Vitamin D functions. We aimed to determine the association between SNPs in the Vitamin D gene cascade and response to pegylated interferon (PegIFN) therapy in hepatitis B e-antigen (HBeAg)-positive patients. One hundred and eleven patients treated for 48 weeks with PegIFN-alfa 2a at 13 hospitals were retrospectively evaluated. Thirteen SNPs derived from Vitamin D cascade-related genes, including DHCR7 (rs12785878), CYP27B1 (rs10877012), CYP2R1 (rs2060793, rs12794714), GC (rs4588, rs7041, rs222020, rs2282679), and VDR (FokI, BsmI, Tru9I, ApaI, TaqI), were genotyped. Thirty-one patients (27.9%) seroconverted to HBeAg after 24 weeks of treatment. Multivariate analysis found pretreatment qHBsAg 10,000 IU/mL (OR = 7.73, 95% CI: 2.36± 25.31, P = 0.001), CYP2R1 rs12794714 TT genotype (OR = 4.16, 95% CI: 1.07±16.25, P = 0.04), and baseline ALT 2 times the upper limit of normal (OR = 3.83, 95% CI: 1.31± 11.22, P = 0.014) predicted sustained HBeAg seroconversion after completion of PegIFN treatment. HBV DNA during study period tended to be lower with the rs12794714 CYP2R1 TT than the non-TT genotype. The rs12794714 CYP2R1 polymorphism may be a useful pretreatment factor predictive of sustained HBeAg seroconversion after PegIFN therapy. This study provides evidence that not only Vitamin D level but also genetic variation of CYP2R1 in the Vitamin D cascade influences host immune response in chronic HBV infection.